2018
DOI: 10.1111/eea.12668
|View full text |Cite
|
Sign up to set email alerts
|

Australian native flowering plants enhance the longevity of three parasitoids of brassica pests

Abstract: Floral resources from native plants that are adapted to the local environment could be more advantageous than the use of nonnative plants. In Australia, there is a dearth of information on the benefits of native plants to natural enemies and their selectivity against pests. Accordingly, we examined the longevity of the parasitoids Diaeretiella rapae (McIntosh) and Cotesia glomerata (L.) (both Hymenoptera: Braconidae), and Diadegma semiclausum (Hellen) (Hymenoptera: Ichneumonidae) exposed to flowering shoots fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Remnant non-crop habitats such as ground cover or wild plants can provide shelter, being a source habitat from which natural enemies can colonize crops 1,5 . The reintroduction of appropriate flowering plants into monocultures can promote longevity, fecundity, sex ratio and searching capacity of natural enemies such as parasitoids [6][7][8][9] . The addition of flowering plants within or around crop fields can enhance the impact of natural enemies by providing nectar, pollen [10][11][12] , alternative hosts or prey 13 , favorable microclimatic conditions 14 and shelter 1,15,16 .…”
mentioning
confidence: 99%
“…Remnant non-crop habitats such as ground cover or wild plants can provide shelter, being a source habitat from which natural enemies can colonize crops 1,5 . The reintroduction of appropriate flowering plants into monocultures can promote longevity, fecundity, sex ratio and searching capacity of natural enemies such as parasitoids [6][7][8][9] . The addition of flowering plants within or around crop fields can enhance the impact of natural enemies by providing nectar, pollen [10][11][12] , alternative hosts or prey 13 , favorable microclimatic conditions 14 and shelter 1,15,16 .…”
mentioning
confidence: 99%
“…It followed closely the design and methodology of Pandey et al . (2018), who emphasised Australian native plants as possible food sources for parasitoids of Brassica pests. When it became obvious that F. arisanus was not floral feeding (see ‘Results’), the study was extended to fruit as another possible carbohydrate source following the work of Stuhl et al .…”
Section: Methodsmentioning
confidence: 99%
“…This experiment was initially designed exclusively as a flower trial, testing different flowers for possible companion planting within or adjacent to orchards to provide nectar sources for F. arisanus. It followed closely the design and methodology of Pandey et al (2018), who emphasised Australian native plants as possible food sources for parasitoids of Brassica pests. When it became obvious that F. arisanus was not floral feeding (see 'Results'), the study was extended to fruit as another possible carbohydrate source following the work of Stuhl et al (2011).…”
Section: Experiments 3: Floral and Other Carbohydrate Sourcesmentioning
confidence: 99%
“…In recent years, however, interest in native plants has increased. Pandey et al (2018) showed the longevity of the parasitoids, Diaeretiella rapae (McIntosh), Cotesia glomerata (L.) (Hymenoptera: Braconidae), and Diadegma semiclausum (Hellen) (Hymenoptera: Ichneumonidae) exposed to flowers of Australian native plants was comparable with the longevity when exposed to the commonly used F. esculentum. Native species can outperform or provide similar resources as nonnatives and have several advantages such as local adaptation, habitat perpetuity, and enhanced native biodiversity value (Fiedler et al 2008).…”
Section: Introductionmentioning
confidence: 96%